Case Report: Anal canal duplication associated with anorectal stenosis-A rare presentation - Zhen Zheng; Zhen Zheng; Dong Xiao; Junxiang Wang; Haozhong Xu; Jianxiong Mao; Xiuliang Wang (Frontiers Media S.A., 2022)
Anal canal duplication is a rare gastrointestinal malformation characterized by extra anal orifices at 6 o'clock in the lithotomy position. To date, there have been only 110 reported cases. The purpose of this study is to contribute two infant cases, one of which is associated with anorectal stenosis, which has never been described.